2021
DOI: 10.1111/jpn.13551
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates molecular structure profiles in relation to nutritional characteristics of newly developed low and normal tannin faba bean varieties in dairy cows analysed by using standard methods and the vibrational molecular spectroscopy (Ft/IR‐ATR)

Abstract: Abbreviations: ADF, acid detergent fibre; ADL, acid detergent lignin; AECP, truly absorbed rumen endogenous protein in the small intestine; AMCP, truly absorbed microbial protein in the small intestine; ARUP, truly absorbed rumen undegradable protein in the small intestine; BSt, rumen bypass or undegraded feed starch; CHO, carbohydrates; CP, crude protein; D, degradable fraction; dBNDF, intestinal digestibility of rumen bypass neutral detergent fibre; dBST, intestinal digestibility of rumen bypass starch; DE 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In a previous study (Rodríguez-Espinosa et al 2021), we reported the faba bean carbohydrate molecular structure profiles and carbohydrate nutritional value and their interactive relationship. However, to our knowledge, there is no detailed information on protein profiles, protein utilization, and availability in faba bean genotypes and lines grown in western Canada nor a study on the interactive relationship between protein molecular structure profiles of these coolseason adapted Vicia faba and its nutritional characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study (Rodríguez-Espinosa et al 2021), we reported the faba bean carbohydrate molecular structure profiles and carbohydrate nutritional value and their interactive relationship. However, to our knowledge, there is no detailed information on protein profiles, protein utilization, and availability in faba bean genotypes and lines grown in western Canada nor a study on the interactive relationship between protein molecular structure profiles of these coolseason adapted Vicia faba and its nutritional characteristics.…”
Section: Introductionmentioning
confidence: 99%